A phase II randomised study of preoperative trastuzumab alone or combined with everolimus in patients with early HER2-positive breast cancer and predictive biomarkers (RADHER trial). (November 2021) - Campone, Mario; Bachelot, Thomas; Treilleux, Isabelle; Pistilli, Barbara; Salleron, Julia; Seegers, Valérie; Arnedos, Monica; Loussouarn, Delphine; Wang, Qing; Vanlemmens, Laurence; Jimenez, Marta; Rios, Maria; et al.
Abstract: Introduction: Resistance to trastuzumab in breast cancer is an ongoing challenge. Clinical and biological effects of co-targeting HER2 and mammalian target of rapamycin (mTOR) in patients with HER2-positive early operable breast cancer via the addition of everolimus to preoperative trastuzumab were evaluated in a phase II randomised study. Methods: Patients were randomised 1:1 to receive trastuzumab (4 mg/kg initial dose then 2 mg/kg weekly for 5 weeks) alone or combined with everolimus (10 mg/day for 6 weeks) and then underwent surgery. Tumours were assessed by clinical examination and echography at the baseline and on treatment. The primary end-point was the clinical response rate at 6 weeks. Pathological response and safety were also evaluated. Baseline and surgery tumour samples were assessed by immunohistochemistry and multiplex immunoanalysis for predictive downstream effectors of the PI3K/AKT/mTOR and MAP kinase (MAPK) pathways. Results: Eighty-two patients were enrolled, 41 per arm. The clinical response rates were 34.1% and 43.9% with trastuzumab alone and combined with everolimus, respectively. Pathological response rates were 43.6% and 47.5%, respectively. Addition of everolimus increased toxicity, notably mucositis (82.5% versus 5.0%) and rash (57.5% versus 10.0%), but grade III/IV events were rare. No correlation between response to treatments and baseline candidate biomarkers was identified, except for PIK3CA mutations which were found to predict trastuzumab resistance. Significant changes were seen in several MAPK pathway effectors after combination therapy. Conclusions: The addition of everolimus did not improve the efficacy, but induced MAPK signalling. Combination therapy to overcome pathway cross-talk should be considered to maximise the effectiveness of trastuzumab in this setting. ClinicalTrial.gov Identifier NCT00674414. Highlights: Eighty-four patients with HER2 breast cancer were included in this multicentric phase II randomised study. This study evaluated the combination of trastuzumab with everolimus given pre-operatively in patients with HER2 breast cancer. No improvement of clinical or pathological response was observed in the combination arm. Only low grade toxicity (World Health Organisation (1-2) was inceased in the combination arm. Changes in the MAPK pathway effectors were observed in the combination arm.